Accelerated FEM Analysis for Critical Engine Components - FRIZZIERO, Leonardo; PIANCASTELLI, Luca (Walailak Journal of Science and Technology (WJST), 2014)
This paper introduces a method to simplify a nonlinear problem in order to use linear finite element analysis. This approach improves calculation time by 2 orders of magnitude. It is then possible to optimize the geometry of the components even without supercomputers. In this paper the method is applied to a very critical component: the aluminium alloy piston of a modern common rail diesel engine. The method consists in the subdivision of the component, in this case the piston, in several volumes, that have approximately a constant temperature. These volumes are then assembled through congruence constraints. To each volume a proper material is then assigned. It is assumed that material behaviour depends on average temperature, load magnitude and load gradient. This assumption is valid since temperatures vary slowly when compared to pressure (load). In fact pressures propagate with the speed of sound. The method is validated by direct comparison with nonlinear simulation of the same component, the piston, taken as an example. In general, experimental tests have confirmed the cost-effectiveness of this approach. doi:10.14456/WJST.2015.12